Multidrug-resistant tuberculosis that required 2 years for diagnosis. (27th March 2012) - Yano, Shuichi; Kobayashi, Kanako; Ikeda, Toshikazu
Abstract : Isoniazid (H) or rifampicin (R) mono-resistant disease can be treated easily and effectively with first-line drugs, while combined H and R resistance (ie, multidrug-resistant tuberculosis (MDRTB)) requires treatment with at least four agents, including a quinolone and an injectable agent. Drug-resistant Mycobacterium tuberculosis strains are reported to be extremely difficult to cultivate invitro. The authors report a case of MDRTB that required 2 years for diagnosis, and was detected only in sputum culture on solid medium. Physicians should consider MDRTB if TB is suspected but pathogens are not detected.